2021
DOI: 10.3389/fcvm.2021.702489
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Dietary Inflammatory Index and Heart Failure: Results From NHANES (1999–2018)

Abstract: Objective: To explore the relationship between dietary inflammatory index (DII) and heart failure (HF) in participants with cardiovascular and cerebrovascular diseases.Methods: NHANES (1998–2018) data were collected and used to assess the association of HF with DII. Twenty-four-hour dietary consumptions were used to calculate the scores of DII. Demographic characteristics and physical and laboratory examinations were collected for the comparison between HF and non-HF groups. Logistic regression analysis and ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 33 publications
1
26
0
Order By: Relevance
“…Third, the DII was calculated based on a single 24-hour dietary recall, which is subject to some chance and recall bias. Nevertheless, this method is currently widely used and validated ( 16 , 33 , 34 ). Forth, due to the limited information in the NHANES database, carbohydrates were jointly taken into account without separating the complex from simple carbohydrates in calculating the DII score ( 83 , 84 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Third, the DII was calculated based on a single 24-hour dietary recall, which is subject to some chance and recall bias. Nevertheless, this method is currently widely used and validated ( 16 , 33 , 34 ). Forth, due to the limited information in the NHANES database, carbohydrates were jointly taken into account without separating the complex from simple carbohydrates in calculating the DII score ( 83 , 84 ).…”
Section: Discussionmentioning
confidence: 99%
“…The DII was calculated from a 24-hour recall of dietary data on day one ( 16 , 33 , 34 ), including the types and amounts of foods and beverages consumed during the 24-hour period preceding the interview (midnight to midnight) collected in the MEC. Data are subsequently used to estimate intakes of energy, nutrients, and other food components from those foods and beverages validated by the Nutrition Methodology Working Group ( 35 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies indicated that a high-fat diet is associated with levels of endogenous estradiol, a risk factor for UF ( 14 ). However, another study in Japan suggests no significant association between fat intake and UF, while alcohol intake increased the risk of UF ( 15 ). The dietary patterns have been proved to be linked with the occurrence of CVDs ( 16 ); therefore, it is plausible that they shared similar risk factors in dietary composition.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, twenty-seven nutrients were used to calculate the DII score ( 16 ): alcohol, vitamin B12/B6, β-carotene, caffeine, carbohydrates, cholesterol, energy, total fat, fiber, folic acid, Fe, Mg, monounsaturated fatty acids (MUFAs), niacin, n-3 fatty acids, protein, polyunsaturated fatty acids (PUFAs), riboflavin, saturated fat, Se, thiamine, vitamin A/C/D/E, and Zn. Additionally, even the numbers of nutrients applied for the calculation of DII is <30, the DII scores are still convincing ( 16 , 17 ).…”
Section: Methodsmentioning
confidence: 99%